Analysis of Entrepreneurship Education in Embedding Entrepreneurship Values in the Family of SME Owners to Grow Entrepreneurial Interest (Study of SME Owners in Rejoso Hamlet, Junrejo District, Batu City) - Fitriyaningsih, Devi; Wahyono, Hari (Classroom Action Research Journal (CARJO), 2019)
The purpose of this study was to determine entrepreneurship education taught by SME owners in Rejoso Hamlet, Junrejo District, Batu City, entrepreneurial values that are instilled by SME owners as parents to their children, interest in entrepreneurship in the child's self after getting an entrepreneurial education. This study uses a qualitative research approach to the type of phenomenological research. The selection of informants uses the snowball sampling method. The techniques used in this data collection are observation, interview, and documentation techniques. To test the validity of the data, checking the data through triangulation of sources to the informants' children, and increasing accuracy. The results of the study are (1) entrepreneurship education in the families of SME owners through three ways, namely internalization, modeling, and habit (2) instilled entrepreneurial values, namely honesty, discipline, hard work, creative, independent, responsibility, cooperation, leadership, dare to take risks (3) the entrepreneurial interest in children has paid off, that is, children are interested in continuing the business owned by their parents or setting up their own businessKeywordsEntrepreneurship Education, Entrepreneurship Values, Entrepreneurial Interest